The Effect of Paras Stone Green Coagulant Preparation and Test Solution Concentration on Azo Dye Removal - siti Hulwati; Qonitah - Fardiyah; Barlah - Rumhayati (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2025)
Paras Stone, a volcanic clay rich in silica (SiO₂) and widely used in Lombok, West Nusa Tenggara (NTB), for sculptures, tombstones, and decorative ornaments, produces significant residual waste during carving. This waste can be repurposed as a natural coagulant for wastewater treatment, though research on its local application remains limited. Azo dyes, particularly prevalent in the textile industry, are produced at an estimated 700,000 tons annually, with 10–15% discharged into wastewater streams, posing serious environmental risks due to their toxic and non-biodegradable nature. This study investigates the removal efficiency of Remazol Red azo dye using Paras Stone under three conditions: non-activated, physically activated, and chemically activated with HCl or H₂SO₄. Chemical activation involved immersing Paras Stone in 3 M HCl or 0.1 M H₂SO₄ solutions with stirring for 2 hours, then rinsing to neutral pH and drying. Coagulation–flocculation experiments were conducted in batch mode, consisting of a 4-minute and 20-minute coagulation phase. The results demonstrated that non-activated Paras Stone achieved the highest dye removal efficiency (95.50%), surpassing samples activated with HCl (91.57%) and H₂SO₄ (92.53%). ANOVA analysis confirmed these differences as statistically significant at the 95% confidence level. The optimum conditions were obtained with a coagulant dose of 2.75 g of Paras Stone and 2.00 g of Opuntia ficus-indica gel, applied at a Remazol Red solution concentration of 30 mg/L. The O. ficus-indica gel, prepared by extracting parenchyma tissue, grinding, centrifuging, and collecting the gel-like supernatant, was a natural flocculant that facilitated the formation of larger flocs and accelerated sedimentation. These findings indicate that non-activated Paras Stone offers an effective, low-cost, and environmentally sustainable alternative for removing azo dyes in textile wastewater treatment.